2006
DOI: 10.1007/11786986_61
|View full text |Cite
|
Sign up to set email alerts
|

Some Results on Matchgates and Holographic Algorithms

Abstract: We establish a 1-1 correspondence between Valiant's character theory of matchgate/matchcircuit [14] and his signature theory of planar-matchgate/matchgrid [16], thus unifying the two theories in expressibility. In [5], we had established a complete characterization of general matchgates, in terms of a set of useful Grassmann-Plücker identities. With this correspondence, we give a corresponding set of identities which completely characterizes planar-matchgates and their signatures. Applying this characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
105
0
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 33 publications
(110 citation statements)
references
References 14 publications
4
105
0
1
Order By: Relevance
“…We give a complete characterization of these symmetric signatures over all bases of size 1. These improve previous results [4] where only symmetric signatures over the Hadamard basis (special basis of size 1) were obtained. This in particular confirms a conjecture by Valiant [18].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…We give a complete characterization of these symmetric signatures over all bases of size 1. These improve previous results [4] where only symmetric signatures over the Hadamard basis (special basis of size 1) were obtained. This in particular confirms a conjecture by Valiant [18].…”
Section: Introductionsupporting
confidence: 86%
“…Our characterization is valid for all fields with sufficiently large characteristic p (including the complex numbers C). These improve previous results [4] where only symmetric signatures over the Hadamard basis, which is a special basis of size 1, were obtained. In [4], those results were proved using properties of Krawtchouk polynomials.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Also he proved an interesting lower bound. This lower bound proof also uses the realizability results from [2,1]. In [3], we showed that this particular restrictive SAT counting problem can also be solved by a holographic algorithm using a basis of size 1.…”
Section: Postscriptmentioning
confidence: 86%
“…Before this paper Valiant already gave matchgate identities [15]. In [1] we achieved a unification of the planarmatchgate/signature theory and the generals-matchgate/character theory, and together with [2] this gives a complete algebraic characterization of all realizable signatures. The general-matchgate/character theory was proposed by Valiant in [16].…”
Section: Postscriptmentioning
confidence: 96%